The Meaning of Animals in the First Farm Revolts: From Kostomarov’s Ukraine to Reymont’s Poland at the Turn of the 20th Century - Thomas Aiello (Text Matters)
In 1945, George Orwell published Animal Farm, a critique of Cold War totalitarianism wherein animals acquire human speech, walk on two legs, and ultimately oppress themselves once gaining power. Its concern for the lived experience of farmed animals is marginal. But it was not the first farm animal revolt. Two decades prior, Polish novelist Władysław Reymont published Bunt (Revolt) about a farm animal uprising in search of equality that degenerates into chaos and abuse of power. It was a metaphor for the Bolshevik takeover in Russia that formed a model for Orwell’s later metaphorical criticism of a different generation of totalitarians. Even earlier, Ukrainian historian Nikolai Kostomarov published his own tale of animal revolution, “Skotskoi Bunt” (“Animal Riot”) in 1880, a story that was given a wider audience upon its republication in 1917, just prior to that same Bolshevik Revolution. The case for Kostomarov’s tale being an allegory for human travails, however, is more difficult to make, and there is linguistic and historical evidence that the story is less concerned with human revolution and more with a case against harming nonhuman animals. Both narratives were written and published in a specific cultural context in time and space that would have created distinct receptions to the works partially based on human political realities, but also rooted in flourishing vegetarian and animal rights movements in Ukraine and Poland at the turn of the 20th century.